Cityspeed: uma ferramenta para coleta e visualiza??o de velocidades veiculares em cidades inteligentes - Damasceno, Adson Vinicius Oliveira (2018)
Mobile crowdsensing allows large-scale data to be collected through many devices that people use in their daily routines. The process of collecting and analyzing information about cities is important to understand problems and to find solutions that reduce complexity and costs compared to other methods, such as video monitoring services, and thus addressing the problem of mobility in urban spaces. This work proposes a public access tool to get and view vehicular speeds in Smart Cities through a mobile application that collects the average instantaneous speed through the sensors present in smartphones and sends these informations to Internet. The developed tool called CitySpeed provides data for traffic analysis that also allows to use filters to view through heatmaps, high and low vehicle speeds on a detailed level, such as road stretches over a period. The selected data can be exported to be used by systems that need data traffic speeds in a city. The results show the use and validation of the tool beyond the data's visualization from experiments realized and let it available publicly through the Internet